Correlated band structure of electron-doped cuprate materials - Dahnken, C.; Potthoff, M.; Arrigoni, E.; Hanke, W. (Физика низких температур, 2006)
We present a numerical study of the doping dependence of the spectral function of the n-type
cuprates. Using a variational cluster-perturbation theory approach based upon the self-energyfunctional
theory, the spectral function of the electron-doped two-dimensional Hubbard model is
calculated. The model includes the next-nearest neighbor electronic hopping amplitude t' and a
fixed on-site interaction U - 8t at half-filling and doping levels ranging from x - 0.077 to x - 0.20 .
Our results support the fact that a comprehensive description of the single-particle spectrum of
electron-doped cuprates requires a proper treatment of strong electronic correlations. In contrast
to previous weak-coupling approaches, we obtain a consistent description of the ARPES
experiments without the need to (artificially) introduce a doping-dependent on-site interaction U.